PENGARUH MEDIA ANIMASI PADA STRATEGI PEMBELAJARAN KONTEKSTUAL TERHADAP KOMPETENSI FISIKA SISWA KELAS XI IPA SMA NEGERI 7 SIJUNJUNG - Febbi Angraini; Hamdi Rifai; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2015)
This article is about the animated media influence on contextual teaching and learning against the competence of physics students of Class XI SCIENCE SMA 7 Negeri Sijunjung. Low competence of physics at SMA Negeri 7 Sijunjung occurs because the students had trouble understanding the concepts of physics that are abstract. Media animation is good media in conveying information that is abstract in the learning process, so it takes an approach that helps in delivering abstract information is becoming more real as contextual teaching and learning. Type of this research is quasi experiments research with Randomized Control Group Only Design. The population of this research is seluruhnya of the grade XI SMA Negeri 7 Sijunjung listed on the school year 2013/2014, sampling techniques using Cluster Random Sampling. Both research class is equally contextual teaching and learning, given the treatment of the animation media is only given in the experimental class of sample 2. Research instrument is the written test for the cognitive aspect, the observation sheet for affective aspect of competence, and scoring rubrics for competency in psychomotor aspect. Influence happens views by using the test of similarity of two average followed by a simple regression test, and test the product-moment correlation on a real level of 0.05. The results showed that indeed the animated media affect the competence of physics students, affects in terms of a better direction. The influence of more high class experimental learning outcomes than the control class on a third aspect of assessment